The Existence of an Audit Committee as a Moderation Among Factors Affecting Audit Quality - Syahrudin, Muhammad (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2022)
Fraud often occurs in manufacturing companies and always experiences changes every year, one of which is financial statement fraud. The existence of financial statement fraud, especially that which occurred in these manufacturing companies, has made public confidence in the reliability of a financial report produced by a Public Accounting Firm (KAP) decreased. This study aims to determine the effect of audit fees. Audit tenure and audit rotation on audit quality as well as to find out how the audit committee is related as a moderating variable to the relationship between the independent variables and the dependent variable. The research method used is descriptive verification using secondary data in the form of financial reports and annual reports of manufacturing companies from the Indonesian Stock Exchange website so that the population is manufacturing companies listed on the Indonesian Stock Exchange with a total sample of 38 companies that have met the sampling criteria. by using purposive sampling method. Methods of data analysis and hypothesis testing the authors use the logistic regression method and Moderated Regression Analysis (MRA) with the support of the SPSS Version 26 program. The results show that there is an effect of audit fees on audit quality, audit tenure and audit rotation have no effect on audit quality. the simultaneous effect of audit fees.